Resistance of heavy metal and antibiotics at industrial effluents and agriculture stagnant water - Twinkal M Patel; Mahesh Chandra Sahu (Apollo Medicine)
Industries are developed day by day. It is required for the development of the country, but industrial pollution is the major problem worldwide. Industrial effluents contain organic, inorganic, radioactive, metals, antibiotics, and carcinogenic substances. Effluents directly or indirectly contact with drinking water and agricultural water and affect human health. Due to metal and antibiotic polluted environment, bacteria developed special resistant mechanism against heavy metal and antibiotic. In future, these bacteria easily survive in high dose and affect humans and agricultural land.